Determination of the in vitro bioaccessibility of phenolic compounds and antioxidant capacity of Juniper berry (Juniperus drupacea Labill.) pekmez - Ozkan, Kubra; Karadag, Ayse; Sagdic, Osman (Tubitak Scientific & Technological Research Council Turkey, 2021)
In this study, the total phenolic content (TPC), total flavonoid content (TFC), in vitro antioxidant capacity and individual phenolic compounds of Juniperus drupacea Labill berry and pekmez (molasses) were determined. Since pekmez was the only edible form of berry, the bioaccessibility of phenolic compounds and the antioxidant capacity of the pekmez were assessed following exposure to simulated gastrointestinal conditions. The phenolic compounds determined in the berry and pekmez were similar, while the pekmez was especially rich in protocatechuic acid, and additionally, the berries were rich catechin and chrysin. Generally, through oral to the intestinal stage of the simulated gastric conditions, the phenolic levels decreased. Although protocatechuic acid was the major phenolic compound at the initial stage, the highest bioaccessibility was observed for catechin and p-hydroxybenzoic acid. In terms of the antioxidant capacity determined by four different methods, the dialyzed fraction (IN) was 0.77-12.19% of the initial values. In this study, detailed information on the antioxidant capacity and phenolic compounds of Juniperus drupacea Labill pekmez and their change through the simulated gastrointestinal conditionswereevaluated for the first-time.
Keywords: Bioaccessibility; in vitro digestion; Juniperus drupacea Labill.; Juniper berry pekmez; phenolics; GASTROINTESTINAL DIGESTION; BIOLOGICAL-ACTIVITIES; STORAGE-CONDITIONS; FOLK MEDICINE; FROZEN PULPS; POLYPHENOLS; EXTRACTS; FRUITS; METABOLISM; STABILITY; Agriculture; Forestry